“Comparativo de la aplicación de diferentes dosis de bioabono obtenido a partir de un biodigestor en el rendimiento de maíz amarillo duro (zea mayz L.) en la E.E.A “el porvenir” - García Gonzales, Estephany (2015)
This research was conducted in the field of Agricultura! Experimental Station "El Porvenir " province of San Martin, in order to evaluate the effect of different doses of biofertilizer obtained from a digester in the agronomic performance and yields in the cultivation of yellow corn (Zea Mayz L.), and identify appropriate productivity such that express higher levels of profitability dose. Design used a randomized complete block ( DBCA ) , which 1 consist of 8 treatments (T1 to this research : 20 % biol, T2 : 40 % of biol, T3: 60% of biol, T4: 80 % T5: 100% biol, T6: 150-100-80 NPK, T7: 100 % biol directed to the floor and T8 : absolute control) and 4 replications. The results were processed and analyzed using the statistical program ASSES e lnfoStad. Treatments that reported the highest yields were T6 (NPK) and T5 (biol 100 % foliar) with 6870 and 6570 kg I ha, with the t6 1 present lower profitability and a B I C ratio less than T5T, expressed by the high cost of production for the treatment t6 with the use of chemical fertilizers, while t5 cost is less due to use of bioles. As for plant height and ear ranks ranged from 205 cm to 182cm for plant height and 105.5 cm (M28T) to 91 cm for ear height, the economic analysis, treatments with use of biol t5 100% foliar and t4 (80 % foliar) are those reporting a net value of 194 7 and 1563 soles, benefit costs 1.9 (T5) and 1.8 (T4) respectively anda return of 97 % and 80 % per hectare. Considering these treatments use biol for increased productivity and higher income. From this the bioles are important for increasing productivity and control of Spodoptera in maize is an alternative to the use of fertilizer and organic insecticide.